Monitoring of aquatic birds and surveillance of avian influenza and Newcastle disease of waterfowls at the National Park of Urmia Lake. Issue 5 (28th June 2022) - Dehgany‐Asl, Saied; Allymehr, Manoochehr; Talebi, Alireza; Yosefi, Omid; Allahyari, Esmaeel
Abstract: Background: Urmia lake, as a national park, is one of the most valuable aquatic ecosystems in the Middle East and quatitative and qualitative changes in Urmia lake water have a great impact on its ecological performance and in the region. Objectives: This project was designed to study the effects of the extent of Urmia lake water surface area on the area size and on the number of aquatic birds of the six selected habitats in 2011–2019. The presence of avian influenza (AI) and Newcastle disease (ND) viruses in migratory aquatic birds together with their impacts on poultry farms as well as on rural birds was also under surveillance in 2018–2019. Methods: Changes of Urmia lake and its impacts on area size of the six selected birds habitats were monitored by GIS. The small monitoring program with circular plot point counts was used for counting of the number of birds of the six selected habitats. At least, 100 samples (oropharyngeal and cloacal swabs) were collected. each sample was placed in a sterile plastic tube containg transport media and assigned with an number and store untill used. Reverse transcription‐polymerase chain reaction (RT‐PCR) and real‐time RT‐PCR test were used for detection of AI and ND viruses in the samples. Results: The results revealed that changes in the water surface area of Urmia lake had a gsignificat impacts on area size and the number of aquatic birds of the six selected habitats. The surveillance results showed that 5% of the samples were AIV positvie while 25% of the samples were pasitive for NDV including 20% for non‐virulent NDV (lNDV) and 5% for virulent NDV (vNDV) strains. Conclusion: This study showed that fluctuation of Urmia lake's water surface area influenced ( p < 0.05) the area size of the six selected aquatic birds' habitats and had a great impacts on the number of the migratory birds. Detection of AIV and vNDV emphesises that the seasonal migratory waterfowls spread AI and vND viruses to the ponds and estuaries as well as to the rural birds and industrialised poultry units around the Urmia lake. Potential public health treats were also discussed. Abstract : Lake Urmia is one of the most valuable aquatic ecosystems in the Middle East and its changes have a significant impact on the environment and control of livestock, poultry and human diseases. The presence of avian influenza (AI) and Newcastle disease (ND) viruses in migratory aquatic birds together with their impacts on poultry farms around the Lake emphasises the induction of consistence surveillance and flawless biosafety protocols and finding solutions to combat zoonotic (potential public health threats) avian diseases.